Strategi Adaptif Financial Well-being Generasi Muda Berdasarkan Digital Financial Literacy - I Gusti Agung Prabandari Tri Putri; Made Irma Dwi Putranti; Ida Bagus Ardhi Putra (Forum Kerjasama Pendidikan Tinggi, 2026)
Financial well-being (FWB) has increasingly become something difficult to achieve among the young generation. Based on the existing conditions, this study aims to explore the factors that quantitatively influence FWB. The analysis involves Digital Financial Literacy (X1), Financial Satisfaction (M1), Financial Behavior (M2), and FWB (Y). The research was conducted in Bali Province using purposive sampling, in accordance with the SEM sample size determination rule, which recommends a sample size of five to ten times the number of variables, resulting in an estimated requirement of 95–190 samples. This study involved 110 respondents, mostly aged 21–26 years, representing the productive age group. Data were analyzed using SEM-PLS with WarpPLS 7.0. The results show that DFL and FB have a positive and significant partial effect on FWB. FB and FS serve as mediators in the relationship between DFL and FWB. However, FS acts as a full mediator, as its partial mediation effect was found to be insignificant. The findings suggest that fostering financial well-being requires addressing both digital financial engagement and psychological dimensions of financial satisfaction. Adequate digital financial literacy ensures that the adoption of digital financial services enhances individuals' perceived security and satisfaction. A key strategic contribution of this study is the development of adaptive strategies for enhancing the FWB of the younger generation. Rather than being standardized, such strategies must be tailored to the specific gaps this demographic faces.